2013
DOI: 10.1160/th12-12-0930
|View full text |Cite
|
Sign up to set email alerts
|

TAFI deficiency promotes liver damage in murine models of liver failure through defective down-regulation of hepatic inflammation

Abstract: Emerging evidence indicates that various haemostatic components can regulate the progression of liver disease. Thrombin-activatable fibrinolysis inhibitor (TAFI) possesses anti-inflammatory properties besides its anti-fibrinolytic function. Here, we investigated the contribution of TAFI to the progression of disease in murine models of chronic and acute liver failure. Chronic carbon tetrachloride (CCL4) administration induced liver damage and fibrosis both in TAFI knockout (TAFI-/-) mice and wild-type controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Thus, for comparison we selected CCl 4 -induced liver fibrosis, wherein the chronic administration of toxicant produces liver fibrosis distinct in pattern from ANIT, and without classic bile duct hyperplasia. 31 Similar to a previous study, 32 hepatic fibrin(ogen) deposits were also observed in WT mice challenged with CCl 4 (8 weeks) in a pattern resembling more the borders of the hepatic acinus ( Figure 4A Despite a marked induction of numerous inflammatory chemokines in livers of ANIT-exposed mice (supplemental Figure 2C-H), we did not observe an effect of ANIT exposure or genotype on the number of hepatic macrophages ( Figure 5A). Of importance, we and others have shown lymphocyte accumulation in livers of ANIT-exposed mice.…”
Section: Resultssupporting
confidence: 89%
“…Thus, for comparison we selected CCl 4 -induced liver fibrosis, wherein the chronic administration of toxicant produces liver fibrosis distinct in pattern from ANIT, and without classic bile duct hyperplasia. 31 Similar to a previous study, 32 hepatic fibrin(ogen) deposits were also observed in WT mice challenged with CCl 4 (8 weeks) in a pattern resembling more the borders of the hepatic acinus ( Figure 4A Despite a marked induction of numerous inflammatory chemokines in livers of ANIT-exposed mice (supplemental Figure 2C-H), we did not observe an effect of ANIT exposure or genotype on the number of hepatic macrophages ( Figure 5A). Of importance, we and others have shown lymphocyte accumulation in livers of ANIT-exposed mice.…”
Section: Resultssupporting
confidence: 89%
“…Intriguingly, concanavalin A challenge, which causes hepatitis, leads to increased mortality in female but not male Cpb2 − / − mice . Chemical challenge with CCl 4 or acetaminophen causes more liver damage in Cpb2 − / − mice than in WT mice . Collectively, these data suggest that CPB2 plays a role in protecting against organ damage, especially in the liver.…”
Section: Roles For Cpb2 Explored In Cpb2−/− Micementioning
confidence: 85%
“…Deficiencies of uPA may also promote cancer progression in experimental models of inflammatory colon cancer [126]. In murine models, deficiency of TAFI has been linked with increased fibrin deposition and inflammation leading to liver damage [127]. Other polymorphisms in TAFI and PAI-1 have been described that may contribute to thrombotic risk, but the strength of their association is unclear (Table 1B).…”
Section: Congenital Defects and Variation In Fibrinolysismentioning
confidence: 99%